Study on Reducing Cogging Torque of Permanent Magnet Synchronous Motor with Fractional-slot Windings - GUO Shuying; LI Kun; PENG Jun (Kongzhi Yu Xinxi Jishu)
It respectively analyzed the mechanism of reducing togging torque for permanent magnet synchronous motor by fractional-slot windings, the fundamental principle of fractional-slot windings and the calculation of windings coefficient. FEM simulation was applied to the open- slot motor for calculating the togging torque through fractional-slot windings motor with the combination of different slots and poles, and then obtained the optimal combination. Via the experimental data of prototypes, the effective of fractional-slot windings on reducing togging torque was verified.